HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN INFEKSI SALUARAN PERNAFASAN AKUT (ISPA) - Rahayu, Ria Muji (Jurnal Kesehatan, 2022)
Acute Respiratory Infection (ARI) is a major cause of infectious disease morbidity and mortality in the world. Nearly four million people die from ARI every year, 98% of which are caused by acute respiratory infections. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of ARI in children under five at the Yosomulyo Public Health Center, Metro Central District, Metro City in 2022. Analytical research method with a cross sectional approach. The population of toddlers aged 7-60 months who visited the Yosomulyo Health Center in May-June amounted to 80 toddlers, taking the sample using accidental sampling technique. The measuring method used is by distributing questionnaires and observations with a measuring instrument in the form of a questionnaire sheet which is analyzed univariately with frequency distribution and bivariate with chi square test. The results of the study on the distribution of the incidence of ARI among toddlers were 43 toddlers (53.75%) and 37 people did not experience ARI (46.25%), most of them did not give exclusive breastfeeding as many as 41 toddlers (51.25%) and exclusive breastfeeding as many as 39 children under five (48.75%). There is a relationship between exclusive breastfeeding and the incidence of ARI with a value of 2count of 7.155 and a value of 2table with dk = 1 of 3.841. The conclusion obtained from this study is the distribution of the incidence of ARI in under five children as many as 43 children (53.75%) and 41 infants not given exclusive breastfeeding (51.25%). There is a relationship between exclusive breastfeeding and the incidence of ARI in toddlers, so it is recommended for health workers at the Yosomulyo Health Center to increase counseling efforts to mothers, especially related to the incidence of ARI and the importance of exclusive breastfeeding for the health of toddlers.